EFFECTS OF LIME TO SULFUR-SULFATE TRANSFORMATION ON OXIC DYSTRUDEPTS AND ITS RELATIONSHIP TO PEANUT PRODUCTION - WIGENA, I GEDE PUTU; RACHIM, A.; SANTOSO, D.; SALEH, A. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2001)
A series of laboratory and field experiments were carried out to study the interaction between lime and sulfur. The laboratory experiment was carried out from June to September 1999 to study sulfur-sulfate transformation using an Oxic Dystrudepts from Jambi Province. The experiment tested 3levels of sulfur (0; 5; and 10 ppm S in soil solution) combined with 2 levels of lime (0 and 1.0 times of exchangeable Al). The experiment was arranged in a randomized complete block design with 3 replicates. The field experiment was done from October 1999 to June of 2000, tested 4 levels of sulfur (0; 2.5; 5.0; and 7.5 ppm S in soil solution) combined with 4 levels of phosphorus (0; 0.01; 0.02; and 0.03 ppm P in soil solution), and 3 levels of lime (0; 0.5; and 1.0 times of exchangeable aluminum). The experiment was arranged in a split plot design with 3 replicates. Lime treatments were used as the main plots and incomplete combinations of sulfur and phosphorus as the sub plots. The incomplete sulfur and phosphorus treatment combination were arrenged based on the Hauser?s simplified concept. Results of the experiments showed that application of sulfur at a rate of 5 ppm S in soil solution increased sulfur transformation almost similar with application of lime at 1.0 time of exchangeable-Al equivalent. At the topsoil layer with low S content, lime application increased sulfur transformation almost 2 folds, namely from 70 to 135 ppm S-SO42-. While at the subsoil layer with higher content of sulfur, the increases of sulfur transformation was almost 1.5 folds, namely from 120 to 160 ppm S-SO42-. The field experiment showed that lime increased peanut seed significantly, from 864 to 1058 kg ha-1. Liming also increased seed quality, which can be seen from the significant increase of amino acids contents of peanut seed, namely methionine, cistine, and cystein. The increases of amino acid contents were 0.56 to 0.75 ppm for methionine, 0.58 to 0.70 for cistine, and 0.39 to 0.54 ppm for cysteine. Sulfur application increased dry pod and seed of peanut. The highest yields of dry pod and seed were 2107 and 1320 kg ha-1, respectively, which were achieved at the lime treatment of 1.0 time exchangeable Al combined with 7.5 ppm S in soil solution. Sulfur application also increased seed quality of peanut, which can be seen from the significant increase of amino acid contents: methionine, cistine, and cysteine. Similar with dry pod and seed yields, the highest increase in amino acid contents of peanut seed was also achieved at the lime treatment at 1.0 time of exchangeable-Al equivalent combined with 7.5 ppm S in soil solution. The increases of amino acid content were 0.60 to 0.88 ppm for methionine, 0.61 to 0.80 ppm for cistine, and 0.48 to 0.62 ppm for cystein.